Critical Synthesis Package: Questionnaire of Site Characteristics and Teaching Behaviours That Enhance Learning in the Ambulatory Setting - Karen Miller (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the properties and applications of The Questionnaire of Site Characteristics (QSC) and Teaching Behaviors that Enhance Learning in the Ambulatory Setting, and (2) a copy of the 2-part survey instrument developed by Karen Schultz, MD. The QSC is a survey instrument in two sections, both using the same Likert-type scale, that can be used to rank order and/or factor analyze variables as they are valued by different levels of medical learners in an ambulatory setting. The Site Characteristics section includes 24 questions, and the Preceptor Behaviors section includes 38. The 1-5 scale is anchored with Very Important to Learning (1) and Not At All Important for Learning (5), with an un-scaled (nominal) option "D", Detrimental for Learning. A non-traditional use of the instrument is as a checklist of attributes to foster self-evaluation or reflection on how sites and faculty habits can be improved.